Determination of total phenolic and flavonoid content of Andrographis paniculata, Zingiber officinale and their combinationsis - Ramonah, Dewi (Media Farmasi Indonesia, 2023)
Sambiloto herbs and red ginger are herbal plants that have been empirically used as medicine. The phenolic and flavonoid compounds in sambiloto herbs and red ginger are efficacious as drugs because they have antioxidant activity. This study aims to determine the total phenolic and flavonoid content of the extracts of sambiloto herbs, red ginger and their combination. Both plants were maceration using ethanol-water 96% v/v at ration 1:5 for 5 days. The extracts of sambiloto herbs and red ginger screened for phytochemicals and thin layer chromatography test showed that contained alkaloids, flavonoids, tannins, saponins, steroids and triterpenoids. In addition, sambiloto herb extract contains androgafolid (Rf 0,66) and red ginger extract contains gingerol (Rf 0,41) and shogaol (Rf 0,89). Continued, the total phenolic and flavonoid content were determined using visible spectrophotometry method.). The highest total phenolic of ethanol extract with combination sambiloto herb : red ginger (1:2) of 153,817 ± 1,474 mg GAE/g. The highest total flavonoid of ethanolic extract with sambiloto herbs of 10,257 ± 0,047 mg QE/g. Based on this research, both extracts have phenolic and flavonoid compounds that have potential as antioxidants.